Ultrasound assisted one pot synthesis of imidazole derivatives using diethyl bromophosphate as an oxidant - Nagargoje, Deepak; Mandhane, Priyanka; Shingote, Savita; Badadhe, Pravin; Gill, Charansingh H. (Ultrasonics Sonochemistry, 2012)
A one pot, three-component condensation of benzoin/benzyl, an aldehyde, and ammonium acetate using diethyl bromophosphate as a mild oxidant is achieved to form trisubstituted imidazole compounds. Under ultrasound irradiation, a smooth condensation occurs to get the 2, 4, 5-triaryl-1H-imidazole compounds in good to excellent yields. The study explores the scope and limitation of diethyl bromophosphate as an oxidant and suggests advantages, viz., simplicity of operation, reduction in time, and an increase in product yields. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diethyl bromophosphate (DEP); Imidazole; One pot synthesis; Ultrasound